Back Cover, Volume 40, Issue 8. Issue 8 (9th August 2019) - Martins, Carla; de Medeiros, Paula Frassinetti V.; Leistner‐Segal, Sandra; Dridi, Larbi; Elcioglu, Nursel; Wood, Jill; Behnam, Mahdiyeh; Noyan, Bilge; Lacerda, Lucia; Geraghty, Michael T.; Labuda, Damian; Giugliani, Roberto; et al.
Abstract : On the Back Cover : The back‐cover image is based on the Research Article Molecular characterization of a large group of Mucopolysaccharidosis type IIIC patients reveals the evolutionary history of the disease by Carla Martins et al., DOI: 10.1002/humu.23752 .